"6 Anatomical Landmarks" Technique for Satisfactory Free-Hand Orbital Reconstruction With Standard Preformed Titanium Mesh. Issue 1 (March 2022) - Canzi, Gabriele; Corradi, Federica; Novelli, Giorgio; Bozzetti, Alberto; Sozzi, Davide
Study Design: Retrospective study. Objective: Resolution of clinical signs and symptoms following orbital fractures depends on the accurate restoration of the orbital volume. Computer-Assisted procedures and Patient Specific Implants represent modern solutions, but they require additional resources. A more reproducible option is the use of standard preformed titanium meshes, widely available and cheaper; with their use quality of results is proportional to the accuracy with which they are positioned. This work identifies 6 reproducible and constant anatomical landmarks, as an intraoperative guide for the precise positioning of titanium preformed meshes. Methods: 90 patients treated at the Maxillofacial Surgery Department, Niguarda Trauma Center, Milan, for unilateral orbital reconstruction (January 2012 to December 2018), were studied. In all cases reconstruction was performed respecting the 6 proposed anatomical landmarks. The outcomes analyzed are: post-operative CT adherence to the 6 anatomical markers and symmetry achieved respect to controlateral orbit; number/year of re-interventions and duration of surgery; resolution of clinical defects (at least 12-months follow-up); incidence of complications. Results: Satisfactory results were obtained in terms of restoration of orbital size, shape and volume. Clinical defects early recovered with a low incidence of complications and re-interventions. Operating times and radiological accuracy have shown a progressive improvement during years of application of this technique. Conclusions: The proposed "6 anatomical landmarks" is an easy free-hand technique that allows everyone to obtain high levels of reconstructive accuracy and it should be a skill of all surgeons who deal with orbital reconstruction in daily clinical activity.